Methamphetamine inhibits antigen processing, presentation, and phagocytosis. - Zsolt Tallóczy; Jose Martinez; Danielle Joset; Yonaton Ray; Attila Gácser; Sima Toussi; Noboru Mizushima; Joshua D Nosanchuk; Harris Goldstein; John Loike; David Sulzer; Laura Santambrogio (PLoS Pathogens)
Methamphetamine (Meth) is abused by over 35 million people worldwide. Chronic Meth abuse may be particularly devastating in individuals who engage in unprotected sex with multiple partners because it is associated with a 2-fold higher risk for obtaining HIV and associated secondary infections. We report the first specific evidence that Meth at pharmacological concentrations exerts a direct immunosuppressive effect on dendritic cells and macrophages. As a weak base, Meth collapses the pH gradient across acidic organelles, including lysosomes and associated autophagic organelles. This in turn inhibits receptor-mediated phagocytosis of antibody-coated particles, MHC class II antigen processing by the endosomal-lysosomal pathway, and antigen presentation to splenic T cells by dendritic cells. More importantly Meth facilitates intracellular replication and inhibits intracellular killing of Candida albicans and Cryptococcus neoformans, two major AIDS-related pathogens. Meth exerts previously unreported direct immunosuppressive effects that contribute to increased risk of infection and exacerbate AIDS pathology.